Peasants in Conflict. the Agrarian Reform of the Popular Unity in Colchagua (Chile) [Campesinos en Conflicto: La Reforma Agraria de la Unidad Popular en Colchagua (Chile)] - Robles-Ortiz, C (Universidad de Valladolid, 2020)
Through a case study dealing with an agrarian province representative of Central Chile’s rural society, this article examines rural workers’ role in the political conflict produced by the implementation of the agrarian reform in Chile under the government of the Popular Unity (1970-73). Focusing on a critical juncture in local politics, which was also relevant in in the national political conflict, this article shows “peasants in conflict”. That is, it demonstrates that different sectors of agricultural workers adopted contradicting political strategies, which reflected their interests and notions of the agrarian reform, and were also the product of alliances with other social and political actors. In light of this, the article also suggests that constructing a plurality of political histories is in order to leave behind generalizations and idealizations about the politics of “peasants”. © 2020 Universidad de Valladolid. All right reserved.
Keywords: Agrarian reform; Chile; Peasants; Popular unity